Challenge of Change : Key issues for a developing society - Sathe, Vasant (Ahmedabad Allied Publishers Private Limited, 1989)
This collection of essays and addresses of Mr. Vasant Sathe highlights his holistic perspective of life itself. Mr. Sathe firmly believes that the human being, endowed with intelligence, has the capacity to evolve further and this can be done only by a harmony of spiritual immediately presupposes that the human being must not accept the condition of a pre- determined destiny. possible only when man relies fully on the use of his intelligence to solve his problems, both within and without. and scientific enquiry. This Further evolution is The biggest challenge to man today is the challenge of survival, which can be met only if mankind keeps before it the ideal of higher evolution to reach the supramental stage as visualised by Sri Aurobindo. Modern technological advances make it possible for mankind to achieve an exponential growth into an altogether new and highly evolved form of human life. But for all this, man must create proper conditions of peace, harmony and development. Above all, he shall have to be honest to himself. India is fortunate in having a rich heritage where the wisdom of our seers from Vedic and Upanishadic times provides spiritual guidance essential even for scientific growth for the future of the human race. However, the voice of India can be better heard only when India becomes politically, socially and economically strong and self-reliant. Mr. Sathe's concern is an India that can and must achieve all-round progress, an India that can and must exert an effective influence in persuading the rest of the world to listen to the ancient wisdom of creating a One World Family, 'Vasudhaiva Kutumbakam'. Imbibing this dictum both in letter and spirit, Mr. Sathe has often expressed his thoughts through writings, speeches, letters and interviews on diverse subjects. These embrace the developments in the turbulent and exciting national life of his generation. The reader will discover a new vision, an adventure in ideas that call for a radical shift in planning perspectives, and a fresh insight into the functional viability of our economy. Though the bulk of this selection is concerned with political and economic aspects of independent India, the reader will not fail to discern Mr. Sathe's deep commitment to the welfare of the people in other spheres too, including the moral and the spiritual, and his remarkable capacity to introspect and analys.
Keywords: Social change